Reasons of postoperative astigmatism - Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
At present, cataract extraction offers great improvement for uncorrected and best corrected visual acuity and rapid postoperative rehabilitation. Cataract surgery is now treated as refractive surgery. Postoperative astigmatism has remained the only obstacle to the achievement of good, uncorrected visual acuity after cataract surgery. Postoperative astigmatism is a very complex clinical problem. The main influence on its appearance has preoperative astigmatism as well as shape and length of anterior chamber opening, suturing technique and wound healing.